A Combined Electrochemical‐Microfluidic Strategy for the Microscale‐Sized Selective Modification of Transparent Conductive Oxides. Issue 3 (4th December 2017) - Lamberti, Francesco; Salmaso, Stefano; Zambon, Alessandro; Brigo, Laura; Malfanti, Alessio; Gatti, Teresa; Agnoli, Stefano; Granozzi, Gaetano; Brusatin, Giovanna; Elvassore, Nicola; Giomo, Monica
Abstract: Surface chemical functionalization of transparent conductive oxides (TCOs) is helpful for a wide range of technological applications, ranging from solar cells to biomedical devices, as it allows to tune the electrical, optical, and morphological properties of TCOs toward the desired goal. The electrochemical grafting technique is a surface modification methodology affording robust coatings with tuneable properties and has the potential to be exploited for modifying TCO surfaces. However, due to technical limitations, like the use of a 3‐electrode cell and the need for low pH‐solutions, this approach has not been recurrently applied. Here a novel electrochemical‐microfluidic combined methodology is used where the use of a microchannel drives the spatially controlled covalent grafting of reagents on a TCO surface. To corroborate the validity of this approach in producing more complex chemical structures localized on selected microscale‐sized areas, where a first electrochemical grafting step takes place, an electrochemical glucose biosensor is realized through a layer‐by‐layer approach that shows a remarkable limit of detection in the micromolar concentration range. The sensing mechanism is based on an efficient electron transfer from glucose to the functionalized TCO surface. Biosensor performance is conveniently tuned by acting on the number of enzymatic units loaded onto the biosensor‐tree. Abstract : An electrochemical‐microfluidic combined methodology to modify transparent conductive oxides (TCOs) is proposed. The production of complex molecular structures, selectively localized in the microscale‐sized areas where electrochemical grafting has taken place is demonstrated by realizing an electrochemical biosensor through a layer‐by‐layer approach. This strategy offers a method to produce customizable TCOs for different applications requiring defined patterning.